Design and Construction of Air Compressor using Locally Sourced Materials (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The increasing demand for compressed air in small-scale industrial and agricultural applications in developing regions necessitates cost-effective and readily accessible technological solutions. This study presents the design, construction, and performance evaluation of a functional air compressor utilizing predominantly locally sourced materials. The primary objective was to develop a durable and repairable compressor that reduces dependency on expensive imported units while maintaining operational efficiency. The compressor system was fabricated using locally sourced plastics (PVC pipes) converted into a reciprocating air pump, coupled with a salvaged electric motor (775 DC). Key components such as the pressure tank were constructed from reinforced mild plastic, while the check valves, pressure gauge, and fittings were sourced from local hardware and automotive parts suppliers. The design prioritized simplicity, thermal efficiency, and safety, incorporating a manually adjustable pressure switch and a spring-loaded safety relief valve. Upon assembly, the compressor underwent rigorous testing to evaluate parameters including maximum achievable pressure, volumetric efficiency, pumping speed, and energy consumption. The results indicated that the locally fabricated unit achieved a maximum pressure of 120 psi with a flow rate of 4.5 CFM, comparable to mid-range conventional compressors. The total production cost was approximately 60% lower than equivalent imported models. This research demonstrates that locally sourced materials can be effectively engineered to produce reliable compressed air systems, offering a sustainable alternative for resource-constrained environments. The study contributes to the body of knowledge on appropriate technology and provides a replicable framework for community-based manufacturing. Recommendations for the further optimization of component’s lifespan and noise reduction are discussed.